Specificity of amino acid-aluminum cluster interaction and subsequent oxygen activation by the above complex - Samanta, Bipasa; Sengupta, Turbasu; Pal, Sourav (Journal of Physical Chemistry C, 2018)
Amino acid aluminum cluster complex has been shown to be a promising oxygen molecule activator and has the potential to dissociate O-O bond on the cluster surface. The study of the complex also reveals specificity of amino acid to aluminum cluster in the above complex, which can be used in the detection of amino acid. The results have been obtained by the density functional theory at the B3LYP/6-311++g(d,p) level of calculation.